الاحتراق الوظيفي لدى الممرضين العاملين في مشفى الأسد الجامعي - داؤد, نسرين (Latakia University Journal -Medical Sciences Series, 2017)
يعتبر التمريض من أكثر الأعمال المجهدة بين المهن التي تقدم خدمات إنسانية واجتماعية, ويتطلب المشاركة والتعاطف بشكل أساسي خلال رعاية المرضى. يواجه التمريض مسؤوليات و تحديات كثيرة, أحدها الاحتراق الوظيفي والذي يوصف بأنه نقص في الطاقة والقوة والموارد مع وجود مطالب كثيرة، وهو يؤثر على كفاءة وإنتاجية العاملين في كل ميدان. لذلك هدفت هذه الدراسة الوصفية إلى تقييم مستوى الاحتراق الوظيفي عند (135) ممرض/ة تم اختيارهم عشوائياً من أقسام مختلفة في مشفى الأسد الجامعي باللاذقية. حيث جمعت البيانات باستخدام مقياس ماسلاش. النتائج: كانت درجة الاحتراق الوظيفي لدى التمريض بشكل عام مرتفعة، ووجدت مستوى عالي من الاجهاد الانفعالي لدى أفراد العينة في أقسام العناية المشددة والعمليات والإسعاف وعند حاملي الإجازة الجامعية، أما تبلد الشخصية كان أعلى عند صغيري السن من التمريض، و كانت درجة الإنجاز الشخصي منخفضه في المناوبة الليلية. لم يتأثر حدوث الاحتراق الوظيفي بكل من الجنس، و الحالة الاجتماعية وعدد سنوات الخبرة في الوظيفة. الخلاصة: أوصت النتائج بدراسة هذه المشكلة بشكل أعمق، مع تحديد العوامل ذات الصلة للحد من الاحتراق الوظيفي عند التمريض. يجب الانتباه لجوانب العمل المؤثرة واتخاذ التداخلات المناسبة.Nursing is considered to be one of the most stressful professions among the human services professions, it need compassion and involvement beyond physical care giving. Nurses have tremendous responsibilities and deal with enormous challenges, Burnout is one of these challenges, it is characterized by decreasing energy, power and resources in the presence of excessive demands. It is one of the factors which influence the efficiency and productivity of the workers and staff in every field. Aim: This descriptive study was aimed to assess burnout among 135 nurses, were randomly chosen, working in various section of Al-Assad university hospital. The data were collected by using a translated version of the Maslach Burnout Inventory-Human Services Survey. Results: Showed high levels of burnout among nurses as general Nurses working in Emergency Room, Intensive Care, Operation Room with Baccholrius degree had high level of Emotional Exhaustio (EE). Nurses young people experienced high level of Depronalization (D). Nurses working in night shift showed low level of Personal Accomplishment (PA(.No statistical significance was found between burnout and gende, marital status, work experience. Conclusions: this problem must be studied more deeply and related factors should be recognized in order to reduce burn out among nurses. Many affected aspects of nurse's job should be noticed and appropriate intervention should be conducted.